Online Learning Platform Effectiveness in West Papua Campus During the Covid-19 Pandemic Period - Ardian Eko Sajaril; Siti Fatimahtun Zahra; Muhammad Rusli (Kusuma Negara Business School, 2020)
The corona virus disease outbreak or more commonly known as Covid-19 is sweeping the world. The Emergency Period for the Spread of the Corona Virus Disease (Covid 19) imposes an online learning from home (BDR) rule that applies to all levels of education which is intended to provide a meaningful learning experience Regarding these rules, West Papua itself has issued a circular letter from the Head of the West Papua Provincial Education Office, Barnabas Dowansiba, which states that all learning activities must be carried out from home. student internet quota, including the unpreparedness of students and lecturers in conducting online learning itself. Therefore, the use of online platforms can vary from campus to campus, all of which lead to the objective of obtaining effective learning during the Covid-19 pandemic. The purpose of this study is to find out which online platforms were effective during the Covid-19 pandemic. Sampling using purposive sampling technique. The results of this study indicate that the recommended online platform is a zoom meeting on the grounds that it is easier to use